2013
DOI: 10.18632/oncotarget.1365
|View full text |Cite
|
Sign up to set email alerts
|

The FAK scaffold inhibitor C4 disrupts FAK-VEGFR-3 signaling and inhibits pancreatic cancer growth

Abstract: Even with successful surgical resection and perioperative chemotherapy and radiation, pancreatic ductal adenocarcinoma (PDA) has a high incidence of recurrence. Tumor cell survival depends on activation of signaling pathways that suppress the apoptotic stimuli of invasion and metastasis. Focal adhesion kinase (FAK) is a critical signaling molecule that has been implicated in tumor cell survival, invasion and metastasis. We have previously shown that FAK and vascular endothelial growth factor receptor 3 (VEGFR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 47 publications
2
26
0
1
Order By: Relevance
“…It has been demonstrated that gemcitabine radiosensitizes pancreatic cancer cells accompanied with apoptosis and autophagy [36, 44-47]. Gemcitabine has also been shown to induce senescence in pancreatic cancer cells [48].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that gemcitabine radiosensitizes pancreatic cancer cells accompanied with apoptosis and autophagy [36, 44-47]. Gemcitabine has also been shown to induce senescence in pancreatic cancer cells [48].…”
Section: Discussionmentioning
confidence: 99%
“…A few examples of well characterized protein–protein interaction inhibitors are SP4206 that disrupts the interaction between interleukin 2 (IL-2) and the α-chain of the IL-2 receptor (IL-2Rα) [39], BH3-mimetic ABT-737 [40] which possesses high-affinity binding to the hydrophobic BH3-binding site of recombinant Bcl-X L , ABT-737, and Nutlins that were found to disrupt MDM2–p53 complexes [41]. By inhibiting the interplay between FAK and VEGFR3, we have previously shown that 1 downregulated major FAK and VEGFR3 tyrosine phosphorylation sites that in turn affect key protein signaling networks associated with cancer cell survival, angiogenesis, and metastasis [32,34]. Here, we have discovered that 29 successfully disrupted the FAK–VEGFR3 interaction and induced apoptotic cancer cell death, thus we anticipate 29 to mimic the overall anti-cancer effects of 1 , albeit at much lower concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…1) which successfully binds and disrupts the FAK–VEGFR3 interaction [31]. Further testing with 1 showed reduction in tumor burden and neovascularization in mouse models of melanoma, breast cancer, pancreatic cancer [32], and glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…Staining procedures were performed as described previously [20]. A positive and negative control was included in each staining.…”
Section: Methodsmentioning
confidence: 99%